10. PERAN INTERNATIONAL TELLECOMMUNICATION UNION DALAM MENGATASI CYBER CRIME DI INDONESIA TAHUN 2011 - 2013 - Ahmad Daniel Kusumah Anshary; Hermini Susiatiningsih; Nadia Farabi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
International Telecommunication Union (ITU) is an organization founded in 1865 with thegoal of developing the technology and Informatics. Indonesia is one country that has anoffice member of ITU since 1984 as a coordination center in the Southeast Asia regionworking together to develop and secure ICT in the countries of Southeast Asia. Thisresearch seeks to analyze the role of ITU in combatting cyber crime rate in Indonesia in2011 - 2013, at which time the level of criminal activity in Indonesia cyber crime hasincreased. By using the method descriptive study, researchers found that the ITU has beeninstrumental in making every effort to develop and secure ICT in Indonesia, but there arefactors that make cyber crime in Indonesia has increased in 2011 - 2013. However afterfurther testing through a variety of data and a pooled analysis, the researchers concludedthat there are barriers that keep cyber crime in Indonesia increased despite the ITU hasbeen instrumental in Indonesia.